Phosphonium Ionic Liquid Promoted Synthesis of 1,5-Benzodiazepines under Ambient Conditions - U. Chopade, Anil; M. Chanda, Bhanu (Asian Journal of Chemistry, 2011)
The development of an environmentally benign green methodology for the synthesis of benzodiazepines using new phosphonium-based ionic liquids without any added catalyst. o-Phenylenediamine undergo condensation with different type of ketone in phosphonium based ionic liquids under mild conditions to afford 1,5-benzodiazepines, yield of the products are excellent.